The Development of L2 (Basque) Oracy Skills Through Dialogic Literary Gatherings. (March 2022) - Santiago-Garabieta, Maite; Villardón-Gallego, Lourdes; García-Carrión, Rocío; Duque, Elena
The acquisition of oral communication skills is essential for lifelong learning and development. Despite their importance, specific approaches oriented to its acquisition and mastery in second languages (L2) are not widely established. Indeed, the prevalence of a monologic classroom discourse still hinders the opportunities to enhance language production. This article analyses the development of L2 oracy skills among secondary school students who have participated in Dialogic Literary Gatherings, a dialogue-based educational action, in Basque. The interactions of five students were observed and analyzed using the Cambridge Oracy Assessment Toolkit. The study also included an interview with the teacher, and a focus group with the participant students. The results show that L2 oracy skills of the students evolve when they participate in these dialogic encounters, especially in the cognitive and socio-emotional areas. Implications for the teaching of L2 spoken language are discussed.